Characterization and functional analysis of β-1,3-galactosyltransferase involved in Cry1Ac resistance from Helicoverpa armigera (Hübner) - Li-li ZHANG; Ge-mei LIANG; Xi-wu GAO; Guang-chun CAO; Yu-yuan GUO (Journal of Integrative Agriculture, 2015)
Carbohydrate chains are the principal antigens by which Bacillus thuringiensis (Bt) identify receptor proteins. The interaction between the antigen and Bt causes a pore in the membrane of midgut epithelial cells of insects. Receptor proteins, such as aminopeptidase N and alkaline phosphatase, are glycoproteins. Cadherin is another cell surface receptor protein which has potential glycosylation sites. Glycosyltransferase is very important for the synthesis and modification of receptor proteins. It can indirectly influence the function of Bt. The 1 950 bp full-length cDNA encoding β-1,3-galactosyltransferase was cloned from the the midgut of Helicoverpa armigera by degenerative PCR combined with RACE techniques (GAL-Harm, GenBank accession no.: GQ904195.1) with two potential N-glycosylation sites (157NNTI160 and 272NKTL275). Protein sequence alignments revealed that H. armigera β-1,3-galactosyltransferase shared high identity with β-1,3-galactosyltransferase in other insect species. The expression level of the β-1,3-galactosyltransferase gene in Cry1Ac-resistant H. armigera larvae was 9.2-fold higher than that in susceptible strain. The function of β-1,3-galactosyltransferase was investigated using RNAi technique. The result showed Cry1Ac enhanced the toxicity against the siRNA-treated larvae compared with non-siRNA-treated ones, which indicated β-1,3-galactosyltransferase played an important role for the insecticidal toxicity of Cry1Ac in H. armigera.